2018
DOI: 10.1073/pnas.1715218115
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-dependent activation of the cell wall synthase PBP2a in Streptococcus pneumoniae by MacP

Abstract: Most bacterial cells are surrounded by an essential cell wall composed of the net-like heteropolymer peptidoglycan (PG). Growth and division of bacteria are intimately linked to the expansion of the PG meshwork and the construction of a cell wall septum that separates the nascent daughter cells. Class A penicillin-binding proteins (aPBPs) are a major family of PG synthases that build the wall matrix. Given their central role in cell wall assembly and importance as drug targets, surprisingly little is known abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 40 publications
0
61
0
Order By: Relevance
“…Interestingly, it was shown that aberrant PBP1a activity can be detected outside the midcell zone in pneumococci lacking MreC or CozE, supporting the model that PBP1a can function autonomously (32). PBP2a, on the other hand, interacts with and is regulated by MacP, a substrate of the global cell cycle regulator StkP (34). The interplay between the two PBPs and their respective partners appears to be specific, as interactions between CozE/PBP2a and MacP/PBP1a have not been detected (32,34).…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, it was shown that aberrant PBP1a activity can be detected outside the midcell zone in pneumococci lacking MreC or CozE, supporting the model that PBP1a can function autonomously (32). PBP2a, on the other hand, interacts with and is regulated by MacP, a substrate of the global cell cycle regulator StkP (34). The interplay between the two PBPs and their respective partners appears to be specific, as interactions between CozE/PBP2a and MacP/PBP1a have not been detected (32,34).…”
Section: Discussionmentioning
confidence: 71%
“…It has been reported that PBP1a forms a complex with CozE, MreC and MreD 40 , and that it coimmunoprecipitates with the cell cycle protein GpsB 41 . Furthermore, it has been shown that PBP2a is regulated by MacP, a substrate of the global cell cycle regulator StkP 42 . The interplay between the two PBPs and their respective partners appears to be specific, as interactions between CozE/PBP2a and MacP/PBP1a have not been detected 40,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that PBP2a is regulated by MacP, a substrate of the global cell cycle regulator StkP 42 . The interplay between the two PBPs and their respective partners appears to be specific, as interactions between CozE/PBP2a and MacP/PBP1a have not been detected 40,42 . Presumably, the specific partners of PBP1a and PBP2a are important for the precise spatiotemporal regulation of their activity.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we did not detect a PBP2B self-interaction. Also, we only found positive results when the PBP2B variants were expressed from the pKT25 plasmid (Figure S4) – this is probably due to the difference in copy numbers between the two plasmids used in the assay and not uncommon in BACTH screens of interactions between PBPs and other proteins (29). We also analysed the interactions using a β-galactosidase assay (Figure 4B), which has the added benefit of providing a quantitative result which can give a hint about the strength of the interaction.…”
Section: Resultsmentioning
confidence: 96%